Entrepreneurs' creative responses to institutional challenges : insider perspectives from Sub-Saharan Africa - Eijdenberg, Emiel L.; Thompson, Neil A. (Emerald points., 2020)
Entrepreneurs' creative responses to institutional challenges in sub-Saharan Africa examines institutional constraints and enablers of Tanzanian and Zambian entrepreneurs in sustainability practices. Exploring how entrepreneurs contribute to societal and environmental well-being despite the challenging institutional context in which they operate.